Pharmacist-led education on beyond-use date (BUD) improves community knowledge at a community pharmacy - Solang, Jonathan Adrian Natanael; Kandou, Grace Debbie; Fatimawali, Fatimawali (Holistik Jurnal Kesehatan, 2026)
Background: Beyond-Use Date (BUD) refers to the time limit for using a medication after the packaging is opened or the medication is prepared, as opposed to the expiration date. Public understanding of BUD remains limited, potentially leading to medication use exceeding safe limits, reducing therapeutic effectiveness, and increasing risks to patient safety. Pharmacists play a strategic role in educating the public through health promotion activities in community pharmacies. Purpose: To determine the effect of education provided by BUD pharmacists on the public's level of knowledge. Method: This study used a pre-experimental design with a single-group pretest-posttest. A total of 44 participants who met the inclusion criteria were selected using random sampling at Rophin Jovins Varma (RJV) Pharmacy. The study procedure included a pretest to measure initial knowledge, followed by education provided by pharmacists about BUD, and a posttest to assess changes in knowledge after the intervention. Data were collected using a 15-question questionnaire. Data were analyzed descriptively to describe the distribution of knowledge levels and inferentially using the Wilcoxon Signed Rank Test to assess differences before and after the intervention. Results: Before the intervention, most respondents had low to moderate levels of knowledge. After the intervention, there was a significant improvement, with the majority of participants achieving a high level of knowledge. Statistical analysis showed a significant difference between pre- and post-intervention knowledge levels. Conclusion: Education provided by pharmacists regarding BUD significantly improved community knowledge. Educational interventions through health promotion activities within the pharmacist community were effective in increasing community understanding of the safe and rational use of medicines. Suggestion: Pharmacists are encouraged to provide ongoing education regarding BUD to promote safe and rational use of medicines.   Keywords: Beyond-Use Date (BUD); Community Knowledge; Community Pharmacy; Pharmacist-Led Education.   Pendahuluan: Beyond-use date (BUD) merupakan batas waktu penggunaan obat setelah kemasan dibuka atau obat diracik, berbeda dengan tanggal kedaluwarsa. Pemahaman masyarakat mengenai BUD masih terbatas, sehingga berpotensi menyebabkan penggunaan obat melewati batas aman, menurunkan efektivitas terapi, serta meningkatkan risiko terhadap keselamatan pasien. Apoteker memiliki peran strategis dalam memberikan edukasi kepada masyarakat melalui kegiatan promosi kesehatan di komunitas apoteker. Tujuan: Untuk mengetahui pengaruh edukasi yang diberikan oleh apoteker BUD terhadap tingkat pengetahuan masyarakat. Metode: Penelitian ini menggunakan desain pre-eksperimental dengan rancangan one group pretest–posttest. Sebanyak 44 partisipan yang memenuhi kriteria inklusi dipilih menggunakan teknik accidental sampling di Apotek Rophin Jovins Varma (RJV). Prosedur penelitian meliputi pre-test untuk mengukur tingkat pengetahuan awal, dilanjutkan dengan pemberian edukasi oleh apoteker mengenai BUD, serta post-test untuk menilai perubahan tingkat pengetahuan setelah intervensi. Data dikumpulkan menggunakan kuesioner yang terdiri dari 15 pertanyaan. Analisis data dilakukan secara deskriptif untuk menggambarkan distribusi tingkat pengetahuan dan secara inferensial menggunakan uji Wilcoxon Signed Ranks Test untuk menilai perbedaan sebelum dan sesudah intervensi. Hasil: Sebelum intervensi, sebagian besar responden memiliki tingkat pengetahuan rendah hingga sedang. Setelah intervensi, terjadi peningkatan yang signifikan, dengan mayoritas partisipan mencapai tingkat pengetahuan tinggi. Analisis statistik menunjukkan adanya perbedaan yang bermakna antara tingkat pengetahuan sebelum dan sesudah intervensi. Simpulan: Edukasi yang diberikan oleh apoteker mengenai BUD secara signifikan meningkatkan pengetahuan masyarakat. Intervensi edukasi melalui kegiatan promosi kesehatan di komunitas apoteker efektif dalam meningkatkan pemahaman masyarakat mengenai penggunaan obat yang aman dan rasional. Saran: Apoteker diharapkan memberikan edukasi berkelanjutan mengenai BUD untuk meningkatkan penggunaan obat yang aman dan rasional.   Kata Kunci: Beyond-Use Date (BUD); Community Knowledge; Community Pharmacy; Pharmacist-Led Education.